Crowd Work und Plattformökonomie - Schneider-Dörr, Andreja (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
This paper addresses the question of whether crowd workers on microtask platforms should be classified as employees. For years, this has been disputed from the perspective of labor law, but with a certain tendency to deny it. However, the BAG ruled in December 2020 that a crowd worker can be an employee by and large. So how are the circumstances to be assessed that make a crowd worker an employee (or non-employee)? That is what this paper investigates.